The contribution of waqf institutions in Malaysia and Turkey in improving the socio-economic conditions of the society - Saad, Norma; Kayadibi, Saim; Hamid, Zarinah (Bulent Ecevit University, 2017)
It has been widely acknowledged that waqf institutions play an important role in the socio-economic development of the Muslim Ummah in the Islamic history. This paper elaborates the contribution of selected waqaf entities in Turkey and Malaysia in improving the socio-economic conditions of the society. The waqaf entities involved in this study include two corporate waqaf institutions from Malaysia, namely Al-Bukhary Foundation and Kumpulan Waqaf An-Nur Berhad; and four waqaf entities in Turkey, namely, IHH Foundation, Diyanet Foundation, Hakyol Foundation, and TIMAV. This study discusses the projects and programs undertaken by these selected waqf entities to achieve their respective objectives. Such a comparison is important considering the diverse experiences of these selected waqaf entities in view of the differences in their endowments and different corporate management models. The paper investigates whether these waqaf entities have implemented a novel approach in developing waqf programs and experimenting new ways of new reaching out to the beneficiaries.